Literasi Anti Hoaks dan Sosialisasi Pelaksanaan Pemilu 2024 pada Generasi Z melalui Webinar - Melati Mediana Tobing (JURNAL ComunitÃ Servizio : Jurnal Terkait Kegiatan Pengabdian kepada Masyarakat, terkhusus bidang Teknologi, Kewirausahaan dan Sosial Kemasyarakatan, 2024)
The fierce competition between political parties and legislative candidates tends to use various methods to win the 2024 elections, including using fake news or hoaxes. Generation Z, who have no experience in conducting general elections, are trapped in a spiral of information on various social media platforms, making it difficult to make their choices and leading to irrational voters and "abstentions". The webinar for digital natives who are fluent in communicating via digital media was carried out 5 days before the 2024 election. The aim was for novice voters as webinar participants to play an active role by becoming anti-hoax agents and being able to convey the procedures for implementing the 2024 election. The webinar method includes public education through presentation of resource material, training in the form of intensive questions and answers, also mediation in the form of quizzes with prizes and filling out questionnaires. Post-test results on 52 participants who filled out the Google form showed that they had made their choice during the webinar and often read news about the 2024 Election. All respondents admitted that they accessed information from digital and electronic media and none used print media. Interestingly, 54% of respondents have the intention in getting involved in politics. Through an open questionnaire, it was discovered that Gen-z respondents had positive hopes for the election winners and future Indonesian leaders.